ANALISIS PESAN DAKWAH DALAM NOVEL RELIGIUS â€œBULAN TERBELAH DI LANGIT AMERIKAâ€ - Wardani, Sri Wahyu; Alawi, Mohammad (UIN Mataram, 2021)
This novel, the split moon in the sky, tells about the events of America and Islam on September 11, 2001, when the relationship between the two changed, Americans flocked to clash with Islam which resulted in many victims falling, mutual suspicion, mutual accusations, and cornering many parties. The media at that time made the most deceptive trick of power, the bad to be so noble and the so noble to be so bad. With this incident, the terms terrorism, radical Islam and Islamophobia emerged which cornered Islam as an extreme religion. The type of research used in this research is library research with a descriptive qualitative content analysis approach. The results obtained are the da'wah messages contained in the novel Bulan Split in the Sky of America, namely the message of aqidah, message of shari'ah and moral and social messages, while the da'wah values ​​in the novel Bulan Split in America's skies are the values ​​of honesty and kindness, the values ​​of worship, and social values.